2020
DOI: 10.3390/molecules25092242
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Barley Straw Fibers as Reinforcement in Fully Biobased Polyethylene Composites: Macro and Micro Mechanics of the Flexural Strength

Abstract: Awareness on deforestation, forest degradation, and its impact on biodiversity and global warming, is giving rise to the use of alternative fiber sources in replacement of wood feedstock for some applications such as composite materials and energy production. In this category, barley straw is an important agricultural crop, due to its abundance and availability. In the current investigation, the residue was submitted to thermomechanical process for fiber extraction and individualization. The high content of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Such effect can be attributed to the deterioration of the fibers as a result of the shearing forces created during the mixing of the phases. This deterioration is increased at larger fiber contents, since the viscosity of the mixture increments, and so do the shearing forces [62].…”
Section: Micro-mechanical Analysismentioning
confidence: 99%
“…Such effect can be attributed to the deterioration of the fibers as a result of the shearing forces created during the mixing of the phases. This deterioration is increased at larger fiber contents, since the viscosity of the mixture increments, and so do the shearing forces [62].…”
Section: Micro-mechanical Analysismentioning
confidence: 99%
“…Hence, coupling agents such as MAPP may not be required for purely stiffening purposes. However, composites containing MAPP were able to withstand higher flexural deformations and in addition, a recent study indicated that the flexural strength of coupled composites was higher than uncoupled [52]. Contrary to the flexural modulus, the analysis of variance (ANOVA) for the flexural deformation revealed significant differences between coupled and uncoupled composites.…”
Section: Analysis Of the Flexural Modulusmentioning
confidence: 97%
“…The specific intrinsic flexural modulus (E F f /ρ F ) of the fibers are also included in Figure 6 to attain the different densities of the fibers. [52], abaca strands [53], hemp strands [61], hemp core residues [54], recycled fibers [32], and glass fibers [53]).…”
Section: Determination Of the Intrinsic Flexural Modulusmentioning
confidence: 99%
See 1 more Smart Citation
“…They show the influence of bagasse fiber fraction on the mechanical properties of the biocomposites as well as the reduction in CO 2 -equivalent emissions from replacing fossil compatibilizers with a bio-based compatibilizers in a cradle-to-gate life cycle analysis. Serra-Parareda et al [ 2 ] studied the feasibility of incorporating barley straw fiber as reinforcement in a bio-based polyethylene to develop a fully bio-based and 100% recyclable material. They analyze the efficiency of barley fibers by the addition of anhydride maleic polyethylene as coupling agent to determine the flexural behavior of the material to determine the suitability of the material for several applications.…”
mentioning
confidence: 99%